Voting procedures and parliamentary representation in the European Parliament - Trumm, Siim (Wiley, 2015)
Parliamentary representation is a fluid concept. Yet, while the behaviour of elected representatives during roll call votes has been widely analysed, we know little about how parliamentarians act when their individual voting choices are not made public. This paper explores the relationship between voting procedures and the likelihood that Members of the European Parliament prioritise the interests of their EP party group versus the interests of their national party. Using an original survey, I find that MEPs are more likely to prioritise the interests of their national party over those of their EP party group when voting by show of hands or electronically, as opposed to by roll call. Moreover, this voting procedure effect is particularly salient among MEPs elected from 2004/07 accession countries.